2022
DOI: 10.1002/psp.2618
|View full text |Cite
|
Sign up to set email alerts
|

Worker intra‐urban residential migration and spatial labour market change in Melbourne's functional economic regions

Abstract: This paper investigates the intra‐urban residential migration of workers in Melbourne and assesses the spatial effects of this dynamic on urban internal structure and spatial labour markets. Intra‐urban migration is an important category of internal migration that relocates human and social capital in urban areas, contributing to changes in urban residential and labour market structure. This paper fills the gap in internal migration literature by determining spatial residential movement dynamics through a spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…Intra-urban migration shapes not only the physical living environment but also the social environment (Keunen and Ley, 2023; Li and Dodson, 2023). While the impacts of intra-urban migration have been widely researched, very little of that research focus on features of intra-urban migration in a Chinese context.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intra-urban migration shapes not only the physical living environment but also the social environment (Keunen and Ley, 2023; Li and Dodson, 2023). While the impacts of intra-urban migration have been widely researched, very little of that research focus on features of intra-urban migration in a Chinese context.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-urban migration or residential mobility refers to migration within an urban area. It has been primarily viewed as an adjustment to spatial housing equilibrium ever since the publication of Rossi’s (1955) classic work (Brown and Moore, 1970; Huang and Deng, 2006; Li, 2004; Li and Dodson, 2023). It is a much more common experience than interregional and international migration, which refers to a change in residential location over longer distances (Li and Dodson, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies also show that the drivers of regional migration and metropolitan migration vary, resulting in different underlying patterns. Migration within metropolitan areas follows the utility maximization principle (Fujita, 1989) and is often associated with household housing change, workplace change, and education factors (Burnley et al, 2007;Li & Dodson, 2023), whereas migration across regional areas is driven by factors such as family ties, economic and career opportunity, environmental quality, and comparative housing affordability (Crommelin et al, 2022;Denham, 2021a;Vij et al, 2021). The relationship between migration and economic opportunities have been examined by regional economists, who found that income, employment opportunity and other financial benefit is an important force driving regional migration (Hunt, 2006;Jennissen, 2003;Rodríguez-Pose & Ketterer, 2012;Simionescu et al, 2016).…”
Section: Literture On Regional Migrationmentioning
confidence: 99%